Differences in maximal strength capacity between isometric squat and mid-thigh pull tests in elite track and field athletes - Stavridis, I.; Fragkoulis, E.; Tsopanidou, A.; Economou, T.; Tsolakis, C.; Koulouvaris, P.; Paradisis, G. (ISBS Proceedings Archive (Michigan), 2021)
The aim of this study was to compare the vertical peak force (PF) generated during the isometric mid-thigh pull (IMTP) and isometric squat (ISqT) performed at the same knee and hip angles. Fourteen elite track and field athletes performed 3 maximal efforts of isometric IMTP and ISqT tests. The vertical PF was measured by a force platform (Kistler 9290CD, AG Winterthur, Switzerland). Our findings revealed significant higher PF and relative PF during ISqT than IMTP (Mean difference: 953 ± 224 N, p < 0.001, d = 1.62 and 14.6 ± 2.4 N.kg-1, p < 0.001, d = 3.8, respectively). The results of this study suggest that ISqT may be more appropriate testing procedure for identifying athletes` maximum isometric strength capacities in elite track and field athletes